Endocardial Approach for Substrate Ablation in Brugada Syndrome: Epicardial, Endocardial or Transmural Substrate? - Tauber, Pablo E. (2018)
Background: Radiofrequency ablation (RFA) in Brugada syndrome (BrS) has been performed both endocardially and epicardially. The substrate in BrS is thus unclear.Objectives: To investigate the functional endocardial substrate and its correlation with clinical, electrophysiological and ECG findings in order to guide an endocardial ablation.Methods: Thirteen patients (38.7±12.3 years old) with spontaneous type 1 ECG BrS pattern, inducible VF with programmed ventricular stimulation (PVS) and syncope without prodromes were enrolled. Before to endocardial mapping the patients underwent flecainide testing with the purpose of measuring the greatest ST-segment elevation for to be correlated with the size and location of substrate in the electro-anatomic map. Patients underwent endocardial bipolar and electro-anatomic mapping with the purpose of identify areas of abnormal electrograms (EGMs) as target for RFA and determine the location and size of the substrate.Results: When the greatest ST-segment elevation was in the 3rd intercostal space (ICS), the substrate was located upper in the longitudinal plane of the right ventricular outflow tract (RVOT) and a greatest ST-segment elevation in 4th ICS correspond with a location of substrate in lower region of longitudinal plane of RVOT. A QRS complex widening on its initial and final part, with prolonged transmural and regional depolarization time of RVOT corresponded to the substrate locateded in the anterior-lateral region of RVOT. A QRS complex widening rightwards and only prolonged transmural depolarization time corresponded with a substrate located in the anterior, anterior-septal or septal region of RVOT. RFA of endocardial substrate suppressed the inducibility and ECG BrS pattern during 34.7±15.5 months. After RFA, flecainide testing confirmed elimination of the ECG BrS pattern. Endocardial biopsy showed a correlation between functional and ultrastructural alterations in two patients.Keywords: Brugada syndrome; Radiofrequency catheter ablation; Electrocardiography; Mapping; Biopsy.Conclusion: Endocardial RFA can eliminate the BrS phenotype and inducibility during PVS.